The 2.3A crystal structure of the antibody Fab HPC-4 in complex with calcium and the epitope peptide. - Garteiser, Philippe. (My University, 2007)
The murine monoclonal antibody HPC-4, directed against the activation region of the human anticoagulant zymogen protein C (PC), is one of the few immunoglobulins known to display calcium-dependent antigen binding. Unlike the more common class of antibodies that merely recognize a calcium-bound conformation of their antigen, HPC-4 interacts directly with calcium in the high affinity PC-HPC-4 complex.

Metal ions can have considerable affinities for proteins, and give rise to geometric constraints that are often taken advantage of in protein-protein interactions. The coordination shell of metal ions can be filled by atoms provided by two different proteins, resulting in a high affinity protein complex. Surprisingly, this highly efficient binding strategy is rarely observed in immunoglobulins, despite the great number of known antibody structures determined in complex with their protein antigens.

The structure reveals a mode of calcium binding which underlies a novel mechanism of metal aided antigen recognition. The ion is located at the antibodyantigen interface, where it functions both as an electrostatic bridge and as a conformational effector of the antibody. The antigen is further stabilized by an extensive and diverse array of interactions spanning a large surface area of contact. Our results provide a structural explanation for many of the observed characteristics of HPC-4, the first member of a unique class of calcium binding antibodies. As such, it represents a significant contribution to the study of interfacial metals and the structural biology of antibodies.

To provide a structural understanding of HPC-4 function and of the particular antibody class to which it belongs, we have solved the X-ray crystal structure of the HPC-4 Fab fragment in ternary complex with its epitope peptide in the presence of calcium at a resolution of 2.3A. Within the crystal, the antigen-binding region is undistorted by crystalline lattice contacts. All complementarity-determining regions and the peptide antigen have well-defined electron density.
Keywords: Immunoglobulins.; Engineering, Biomedical.; Metal ions.; Antigen-antibody reactions.